2013
DOI: 10.1603/ec12370
|View full text |Cite
|
Sign up to set email alerts
|

Use of Fluorescence, a Novel Technique to Determine Reduction in <I>Bemisia tabaci</I> (Hemiptera: Aleyrodidae) Nymph Feeding When Exposed to Benevia and Other Insecticides

Abstract: The sweet potato whitefly, Bemisia tabaci (Gennadius), is an economically important pest in the United States and other countries. Growers in many places rely on the use of insecticides to reduce populations of B. tabaci. However, insecticides may take a few days to cause B. tabaci mortality and some do not reduce feeding before death. Earlier reduction of feeding of whiteflies would decrease the physiological effects on plants, reduce the production of sooty mold and potentially reduce the transmission of vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 18 publications
2
26
0
3
Order By: Relevance
“…The same authors (2013b) measured a reduction in the number and duration of probes by Frankliniella fusca (Thysanoptera: Thripidae) feeding on pepper treated with cyantraniliprole. Cameron et al (2013) used fluorescent dye to show feeding reduction on the part of B. tabaci nymphs on cotton treated with cyantraniliprole. In addition, settling and feeding behavior of Diaphorini citri Kuwayama (Hemiptera: Psyllidae) was reduced on citrus treated with cyantraniliprole (Tiwari & Stelinski 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The same authors (2013b) measured a reduction in the number and duration of probes by Frankliniella fusca (Thysanoptera: Thripidae) feeding on pepper treated with cyantraniliprole. Cameron et al (2013) used fluorescent dye to show feeding reduction on the part of B. tabaci nymphs on cotton treated with cyantraniliprole. In addition, settling and feeding behavior of Diaphorini citri Kuwayama (Hemiptera: Psyllidae) was reduced on citrus treated with cyantraniliprole (Tiwari & Stelinski 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, where fluorescence was used to determine the feeding cessation of B biotype B. tabaci nymphs, plants treated with cyantraniliprole also caused a significant reduction of feeding when compared with nymphs feeding on plants treated with imidacloprid or spirotetramat [34]. Another study showed a reduction in the amount of honeydew produced by B biotype B. tabaci adults in cyantraniliprole treatments equivalent to imidacloprid.…”
Section: Discussionmentioning
confidence: 99%
“…The new diamide insecticide cyantraniliprole (DuPont Cyazypyr), a ryanodine receptor agonist, both controls B. tabaci population and interferes with pest feeding behavior (Cordova et al 2006, Cameron et al 2013). Recent Þeld trials on different crops conÞrm the direct action of this insecticide on B. tabaci populations in Italy (Wiles et al 2012) and India (Mandal 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Recent Þeld trials on different crops conÞrm the direct action of this insecticide on B. tabaci populations in Italy (Wiles et al 2012) and India (Mandal 2012). With the use of a ßuorescent technique, Cameron et al (2013) recently demonstrated that cyantraniliprole produced a signiÞcant reduction of B. tabaci nymphs feeding when compared with nymphs fed on plants treated with other insecticides such as imidacloprid or spirotetramat. In addition, cyantraniliprole is not affected by commonly occurring resistance mechanisms that are known to confer resistance to other insecticide chemistries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation